J. CHINCHÓN ÁLVAREZ, Derecho internacional y transiciones a la democracia y la paz. Hacia un modelo para el castigo de los crímenes pasados a través de la experiencia iberoamericana, Madrid, Ediciones Parthenon, 632 pp. - López Barrero, Esther (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2007)
In January 2004 took place the debate conducted under the auspices of the Bava rian Catholic Academy between then Cardinal Ratzinger and the influential defen der of Laicism, Philosopher Jürgen Habermas about the links between Religion and Politics in our days. The dialogue nevertheless was not at all tense. Surprisingly, for the most part, the coincidences were more than the discrepancies. In this essay, the author tries to evidence the culminating guidelines of that event.